MEDIA ULAR TANGGA 3 DIMENSI UNTUK KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS X SMA - Dwi Yanti, Ani (LATERNE, 2018)
Based on the student needs questionnaires that has been spread in the class X MIA 5 SMAN 3 Lamongan, there are 60.71% of students who have difficulty writing German sentences. Then as many as 57.14% of students said who are interested in game of learning media. Therefore, it takes a media that can help students write German sentences. 3-dimensional snakes and ladders media is a modification form of the snakes and ladders into 3 dimensional form. There are vocabulary and pictures in 3-dimensional snakes and ladders media that can help students write German sentences. This study has a problem “How to develop 3-dimensional snakes and ladders media for learning German language writing skill of student class X SMA?”. The purpose of this study is to describe the development process of 3-dimensional snakes and ladders media for learning German language writing skill of student class X SMA. The steps of media development in this study use Sadiman’s theory but only until validation. The development process of 3-dimensional snakes and ladders media are : (1) pre-production, (2) production, and (3) post-production. The result of this study are: (1) media quality based on expert media validator assessment get 91,25% value with “very good” quality and require little revision, (2) media quality based on expert materi validator assessment get 90% value with “very good” and can be used without revision. Based on the validation result, it can be concluded that 3-dimensional snakes and ladders media developed feasible to be used for learning to write German language class X SMA. Keywords: media, snakes and ladders, 3 dimensions, writing skill.